Pelatihan Pengolahan Limbah Jagung Menjadi Pupuk Sebagai Wujud Tanggung Jawab Iman Kristen Terhadap Lingkungan - Adventus Charles Hamonangan Lumbantobing (LPPI UMN AL WASHLIYAH, 2025)
Agricultural waste management constitutes a significant environmental challenge, impacting both soil fertility and overall environmental quality. From an ecotheological perspective, humans have a moral and spiritual responsibility to care for God's creation, and therefore, the management of agricultural waste can be understood as a form of stewardship. This study aimed to enhance the community's knowledge and skills in Adaran Hutamora Village for processing corn waste into organic fertilizer. A participatory approach was employed, including interactive lectures, group discussions, and hands-on practice with 15 farmer participants. The results of the activity indicated that the participants were able to follow each stage of processing corn waste into dry organic fertilizer, including collection, chopping, drying, mixing with additional materials, grinding, and packaging, while also demonstrating an improvement in understanding and skills. Group discussions and hands-on practice also fostered awareness of the importance of sustainable waste management and responsible stewardship of God's creation. The processing of corn waste into organic fertilizer not only supports sustainable agriculture and enhances soil fertility but also reinforces the community's awareness of the spiritual values of stewardship within ecotheology.